Land-sea correlations in the Eastern Mediterranean region over the past c. 800 kyr based on macro- and cryptotephras from ODP Site 964 (Ionian Basin) - Vakhrameeva, Polina; Koutsodendris, Andreas; Wulf, Sabine; Portnyagin, Maxim; Appelt, Oona; Ludwig, Thomas; Trieloff, Mario; Pross, Jörg (Quaternary science reviews, 2021)
Direct correlations between terrestrial and marine climate-proxy records are essential in order to determine potential lead/lag relationships in the response of the terrestrial and marine realms to climate forcing. In the Eastern Mediterranean region, such land-sea correlations have not yet been established beyond c. 200 ka. To explore the potential of tephra layers for Late and Middle Pleistocene land-sea correlations in the Eastern Mediterranean region, we have revisited yet unconfirmed tephra layers previously reported from Ocean Drilling Program (ODP) Site 964 (Ionian Basin) for the past c. 800 kyr in order to identify their origin and examine potential terrestrial counterparts. Using major- and trace-element glass analyses, we confirmed the presence of seven visible tephra layers with ages from 623 to 38 ka. These tephra layers represent known tephra isochrons from Italian volcanic centers (Y-5, Y-7, X-6, and V-0) and three yet unknown eruptions from Etna (623 ka), the Campanian Volcanic Zone (CVZ; 238 ka), and Pantelleria (238 ka). Because the majority of the previously reported tephra layers from ODP Site 964 were identified as clastic layers of non-volcanic origin, cryptotephra analyses were carried out for cores spanning Marine Isotope Stages (MIS) 13 to 9 (500-320 ka). This effort yielded 19 cryptotephra layers originating from Santorini volcano, the CVZ, possibly Roccamonfina volcano, and an undefined source in either the Aeolian Islands or the South Aegean Volcanic Arc. Two tephra layers are correlated with potential equivalents from terrestrial archives on the Italian and Balkan Peninsulas, including tephra isochrons SC5/A7/OH-DP-1966 (c. 493 ka; Mercure basin, Acerno basin, and Lake Ohrid) and TP09-65.95 (c. 359 ka; Tenaghi Philippon) that represent an unknown eruption of Roccamonfina and the Cape Therma 1 eruption of Santorini, respectively. Direct linking of the marine record from ODP Site 964 with the terrestrial records from Tenaghi Philippon, Lake Ohrid, and the Acerno basin via tephra tie points allowed us to circumvent shortcomings of the individual age models, and to obtain a comprehensive picture of climate variability in the greater Eastern Mediterranean region for the MIS 13-9 interval.
Available online 9 February 2021
Gesehen am 30.06.2021